Paul’s Use of Deuteronomy in Galatians 3: A Rhetorical and Intertextual Analysis - Emmanuel Actor Oyewole (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This article argues that Paul’s use of Deuteronomy 27:26 and 21:23 in Galatians 3:10–14 is neither incidental nor merely evidential but constitutes the decisive rhetorical and theological pivot of his argument for justification by faith. Against readings that treat Paul’s citations as prooftexts supporting a pre-formed theology, this study contends that Paul actively reconstructs the Deuteronomic curse tradition to expose the internal logic of law-based righteousness and to articulate its redemptive resolution in Christ. Employing a rhetorical–intertextual methodology that combines close Greek exegesis with comparative analysis of the Septuagint and Hebrew texts, the article demonstrates that Deuteronomy 27:26 functions to totalise the law’s demand and universalise its curse, while Deuteronomy 21:23 is deliberately reappropriated to present the crucified Christ as the covenantal representative who bears that curse on behalf of others. The study concludes that Paul does not abolish the law but redefines its theological function, transforming curse from a terminal judgment into the means by which Abrahamic blessing and Spirit-empowered life are realised through faith.